Sagot :
Answer:
\color{maroon}{\huge{ \tt{Solution:}}}Solution:
Simplify the expression:
\color{cyan}{ \tt{1.)}}1.)
\begin{gathered} \tt{ - 12 {k}^{2} + 7m - 3 + 4 {k}^{2} - 3m } \\ \tt{ = - 8 {k}^{2} + 7m - 3 - 3m } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \boxed{\tt{ = - 8 {k}^{2} + 4m - 3}} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \end{gathered}
−12k
2
+7m−3+4k
2
−3m
=−8k
2
+7m−3−3m
=−8k
2
+4m−3
-----------------|«•»|-----------------
\color{cyan}{ \tt{2.)}}2.)
\: \: \: \: \: \tt{ - 6 {m}^{2} + 3m + 9 - (3 {m}^{2} - 9m + 6)}−6m
2
+3m+9−(3m
2
−9m+6)
\: \tt { = - 6 {m}^{2} + 3m + 9 - 3 {m}^{2} + 9m - 6 }=−6m
2
+3m+9−3m
2
+9m−6
\begin{gathered} \tt{ = - 9 {m}^{2} + 3m + 9 + 9m - 6 } \\ \tt{ = - 9 {m}^{2} + 3m + 9 - 6} \: \: \: \: \: \: \: \: \: \: \\ \tt{ =9 {m}^{2} + 12m + 9 - 6 } \: \: \: \: \: \: \: \: \: \: \: \\ \boxed{\tt{ = 9 {m}^{2} + 12m + 3}} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \end{gathered}
=−9m
2
+3m+9+9m−6
=−9m
2
+3m+9−6
=9m
2
+12m+9−6
=9m
2
+12m+3
-----------------|«•»|-----------------
\color{cyan}{ \tt{3.)}}3.)
\begin{gathered} \tt{(4 {x}^{2} + 3 {x}^{2} + 9x - 10) + (- 2x + 15x)} \\ \tt{ =(7 {x}^{2} + 9x - 10 ) + ( - 2x + 5x) } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \tt{ = (7 {x}^{2} + 9x - 10 ) + (3x)} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \tt{ = 7 {x}^{2} + 9x - 10 + 3x} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \boxed{\tt{ = 7 {x}^{2} + 12x - 10 } } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \end{gathered}
(4x
2
+3x
2
+9x−10)+(−2x+15x)
=(7x
2
+9x−10)+(−2x+5x)
=(7x
2
+9x−10)+(3x)
=7x
2
+9x−10+3x
=7x
2
+12x−10
-----------------|«•»|-----------------
\color{cyan}{ \tt{4.)}}4.)
\begin{gathered} \tt{(5x - 3x + 2x) - (4x + 2 {x}^{2} + 2x + 3x + 9 )} \: \: \\ \tt{ = (4x) - (9x + 2 {x}^{2} + 9 )} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \tt{ = 4x - 9x - 2 {x}^{2} - 9 } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \tt{ = - 5x - 2 {x}^{2} - 9 } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \boxed{\tt{ = - 2 {x}^{2} - 5x - 9}} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \end{gathered}
(5x−3x+2x)−(4x+2x
2
+2x+3x+9)
=(4x)−(9x+2x
2
+9)
=4x−9x−2x
2
−9
=−5x−2x
2
−9
=−2x
2
−5x−9
-----------------|«•»|-----------------
\color{cyan}{ \tt{5.)}}5.)
\begin{gathered} \tt{(4abc + 3ab + abc) - (6abc + 7bc - 15 )} \\ \tt{ = (5abc + 3ab) - (6abc - 7bc + 15)} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \tt{= 5abc + 3ab - 6abc - 7bc + 15} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \boxed{ \tt { = - abc + 3ab - 7bc + 15}} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \end{gathered}
(4abc+3ab+abc)−(6abc+7bc−15)
=(5abc+3ab)−(6abc−7bc+15)
=5abc+3ab−6abc−7bc+15
=−abc+3ab−7bc+15
-----------------|«•»|-----------------
\color{maroon}{\huge{ \tt{Answer:}}}Answer:
Perform the indicated operation ( Add or Subtract). Show your solution.
\tt{1.) \: \underline{ \boxed{ \tt{ - 8 {k}^{2} + 4m - 3 }}} }1.)
−8k
2
+4m−3
\tt{2.) \: \underline{ \boxed{ \tt{ - 9 {m}^{2} + 12m + 3 }}} }2.)
−9m
2
+12m+3
\tt{3.) \: \underline{ \boxed{ \tt{ 7 {x}^{2} + 12x - 10 }}} }3.)
7x
2
+12x−10
\tt{4.) \: \underline{ \boxed{ \tt{ - 2 {x}^{2} - 5x - 9}}} }4.)
−2x
2
−5x−9
\tt{5.) \: \underline{ \boxed{ \tt{ - abc + 3ab - 7bc + 15}}} }5.)
−abc+3ab−7bc+15
-------------------|«•»|-------------------
» Noelquimba42
» Aliyah1732
-------------------|«•»|-------------------